2022
DOI: 10.1136/bmj-2021-068714
|View full text |Cite
|
Sign up to set email alerts
|

Sintilimab versus placebo in combination with chemotherapy as first line treatment for locally advanced or metastatic oesophageal squamous cell carcinoma (ORIENT-15): multicentre, randomised, double blind, phase 3 trial

Abstract: ObjectiveTo evaluate sintilimab versus placebo in combination with chemotherapy (cisplatin plus paclitaxel or cisplatin plus 5-fluorouracil) as first line treatment of unresectable locally advanced, recurrent, or metastatic oesophageal squamous cell carcinoma.DesignMulticentre, randomised, double blind, phase 3 trial.Setting66 sites in China and 13 sites outside of China between 14 December 2018 and 9 April 2021.Participants659 adults (aged ≥18 years) with advanced or metastatic oesophageal squamous cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
241
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(251 citation statements)
references
References 28 publications
9
241
0
1
Order By: Relevance
“…In the ORIENT-15 trial, 659 patients were randomly divided into sintilimab combined with chemotherapy and placebo combined with chemotherapy. The ORR and median OS of the sintilimab group were better than those of the placebo group (66.1% vs. 45.5%, 16.7 months vs. 12.5 months) [ 26 ]. The ORR of all populations in this study was 60%, which was lower than 66.1% of ORIENT-15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ORIENT-15 trial, 659 patients were randomly divided into sintilimab combined with chemotherapy and placebo combined with chemotherapy. The ORR and median OS of the sintilimab group were better than those of the placebo group (66.1% vs. 45.5%, 16.7 months vs. 12.5 months) [ 26 ]. The ORR of all populations in this study was 60%, which was lower than 66.1% of ORIENT-15.…”
Section: Discussionmentioning
confidence: 99%
“…ORIENT-15 trial showed that grade 1-2 treatment-related AEs of sintilimab combined with chemotherapy were mainly anemia, decrease in white blood cell count, nausea, and vomiting. The most common grade 3-4 AEs were neutropenia, leukopenia, and anemia [ 26 ]. Treatment-related AEs in this study were similar to ORIENT-15 results, except for the incidence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study published in BMJ by Lu et al 1 has reported the interim findings from the ORIENT-15, which is a global, multi-center and randomized phase 3 trial to compare chemoimmunotherapy to chemotherapy alone as first-line treatment in advanced esophageal squamous cell carcinoma (ESCC), and provoked thinking about the chemotherapy regimens for chemoimmunotherapy combinations.…”
mentioning
confidence: 99%
“…Immune-checkpoint blockades (ICB) have been added to chemotherapy in advanced esophageal cancers in multiple clinical trials. The KEYNOTE-590 (pembrolizumab), ESCORT-1st (camrelizumab), CheckMate-648 (nivolumab), JUPITER-6 (toripalimab), and ORIENT-15 (sintilimab) 1 trials all showed superior response and survival for chemoimmunotherapy. These results provided solid evidence for chemoimmunotherapy as first-line treatment of advanced ESCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation